1996
DOI: 10.1088/0953-8984/8/20/006
|View full text |Cite
|
Sign up to set email alerts
|

Electronic topological transition in zinc metal at high external pressure

Abstract: We report investigations of Zn metal under quasi-hydrostatic pressures up to 16 GPa by 67 Zn Mössbauer spectroscopy and scalar-relativistic linearized augmented plane wave (LAPW) calculations. Our studies show that at 4.2 K an electronic topological transition (ETT) occurs at about 6.6 GPa, corresponding to a volume change of (1−V /V • ) ≈ 0.085. At the ETT conduction electron states in the third Brillouin zone at the symmetry point L ('butterflies') move below the Fermi surface and start being occupied. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 45 publications
(91 reference statements)
3
33
3
Order By: Relevance
“…On the other hand, if an anomaly in c/a does exist, it is very likely to induce a corresponding anomaly in V zz . This simply follows from the results of the same authors [77], which show that the main contribution to the decrease of the EFG in hcp Zn under external pressure is essentially determined by the decrease of c/a. To resolve this controversy, we calculated the pressure dependence of EFG using our optimized c/a values for all volumes considered and for both metals.…”
Section: Hexagonal Close-packed Zinc Under Pressurementioning
confidence: 62%
See 4 more Smart Citations
“…On the other hand, if an anomaly in c/a does exist, it is very likely to induce a corresponding anomaly in V zz . This simply follows from the results of the same authors [77], which show that the main contribution to the decrease of the EFG in hcp Zn under external pressure is essentially determined by the decrease of c/a. To resolve this controversy, we calculated the pressure dependence of EFG using our optimized c/a values for all volumes considered and for both metals.…”
Section: Hexagonal Close-packed Zinc Under Pressurementioning
confidence: 62%
“…Takemura [75] has shown that the volume dependence of c/a in Zn changes its slope at V/V 0 = 0.893 (P = 9.1 GPa), while Potzel et al [76] found a drastic drop (by a factor of 2) of the Lamb-Mössbauer factor, indicating a drastic softening of low-frequency acoustic and optical phonons at V/V 0 ≈ 0.915 (P = 6.6 GPa). A change in the curvature of the electric field gradient (EFG) dependence on pressure was also observed [76,77].…”
Section: Hexagonal Close-packed Zinc Under Pressurementioning
confidence: 85%
See 3 more Smart Citations